PENGARUH KEBIJAKAN PEMERINTAH TERHADAP HARGA PANGAN DI MALUKU UTARA - Rachman, Sitra Anna A; Tjokrodiningrat, Suryati; Sapsuha, Yusri; Sjafani, Nur; Sudjud, Suratman; Rasulu, Hamidin (Jurnal Pertanian Khairun, 2024)
The government implements a price control policy to protect producers and consumers while simultaneously reducing the rate of inflation by providing subsidies to companies that produce basic necessities and newly developing companies to reduce production costs so they can compete with imported products. The aim of this research is to analyze the influence of government policy on food prices in North Maluku (North Maluku Province, Ternate City and Central Halmahera Regency. Analyze the influence of government policy on food supply in North Maluku. And analyze the influence of government policy on people's purchasing power in North Maluku. The method used in this research is a descriptive method with a simple quantitative and qualitative approach. The research results which have been analyzed with Part Least Square (PLS), using the SmartPLS 4 application tool, show that Government Policy Intervention has a real or significant effect on Food Prices in the City. Ternate and Central Halmahera Regency, then (H1: accepted). So it can be explained that there is a direct influence of government policy intervention variables on food prices in Ternate City and Central Halmahera Regency. Government Policy Intervention has no real effect on Food Supply in Ternate City and Regency Central Halmahera has no real effect or (H0: rejected). And Government Policy Intervention has no real effect on People's Purchasing Power or (H0: rejected). In conclusion, government policy has a significant impact on food prices in the North Maluku region. For this reason, it needs to be optimized through subsidy policies, price regulation, distribution and logistics, agricultural support, and import management. The government also needs to make efforts to ensure the availability of sufficient food supplies at affordable prices for the community. With the right policies, local governments can help stabilize food prices and increase food security in the North Maluku region.Keywords: Government Policy, Food Prices, North Maluku